2022
DOI: 10.3389/fmicb.2022.985725
|View full text |Cite
|
Sign up to set email alerts
|

Structural characteristics of locust bean gum hydrolysate and its alleviating effect on dextran sulfate sodium-induced colitis

Abstract: BackgroundUlcerative colitis (UC) is an inflammatory lesion of the colon from various causes. As current therapeutic drugs have adverse effects on patients with UC, there is a growing demand for alternative medicines from natural and functional foods. Locust bean gum, as a dietary fiber, has a variety of physiological effects.MethodsIn the present study, locust bean gum hydrolysate (LBGH) was obtained from the acid hydrolysis of locust bean gum. The structure of LBGH was characterized by thin-layer chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…We noted active induction of FOS utilization genes by previously described consumers including Bacteroides, Coprococcus, Dorea, Faecalibacterium, and Roseburia (24,58,59). We also saw induction of GM utilization genes in Blautia, Coprococcus, and Ruminococcus, also previously shown to metabolize GM (52,(68)(69)(70)(71). This is not surprising since both glycans have been well studied, with the CAZymes required for the hydrolysis of either glycan described in several bacterial taxa (24,51,52,59).…”
Section: Discussionsupporting
confidence: 54%
“…We noted active induction of FOS utilization genes by previously described consumers including Bacteroides, Coprococcus, Dorea, Faecalibacterium, and Roseburia (24,58,59). We also saw induction of GM utilization genes in Blautia, Coprococcus, and Ruminococcus, also previously shown to metabolize GM (52,(68)(69)(70)(71). This is not surprising since both glycans have been well studied, with the CAZymes required for the hydrolysis of either glycan described in several bacterial taxa (24,51,52,59).…”
Section: Discussionsupporting
confidence: 54%
“…It is well-known that Akkermansia has beneficial effects on intestinal inflammation. 46 Moreover, our results demonstrated that butyric acid was positively correlated with Muribaculum . Recent studies showed that Muribaculum is a major mucin monosaccharide forager, which could hinder Clostridioides difficile colonization and impair pathogen colonization to maintain intestinal homeostasis at the same time.…”
Section: Discussionmentioning
confidence: 51%
“…For instance, some recent experimental evidence noted a marked increase in the intestinal abundance of A. muciniphila in DSSinduced colitis mice compared with healthy controls. [17][18][19][20][21][22][23] In addition to UC, this phenomenon was also seen in some neurodegenerative disorders, such as multiple sclerosis 54,55 and Parkinson's disease. 56,57 Our study also observed an elevated level of gut A. muciniphila in DSS-treated rats, although no significant difference was seen between the control and DSS groups (ESI Fig.…”
Section: Papermentioning
confidence: 99%
“…Akkermansia muciniphila (A. muciniphila) is a mucin-degrading bacterium that has often been detected in the gut of humans and animals with UC. 12 Some studies have reported a reduction in the abundance of A. muciniphila, [13][14][15][16] while others have observed the opposite trend, [17][18][19][20][21][22][23] suggesting a potential negative or positive correlation with UC. More importantly, these correlations have been further confirmed by some interventional studies showing that the consumption of A. muciniphila can alleviate 24,25 or aggravate [26][27][28] disease process, indicating that it has a dichotomous role in UC.…”
Section: Introductionmentioning
confidence: 99%